2017
DOI: 10.1111/echo.13467
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of longitudinal left ventricular function in patients with coronary artery ectasia and vitamin D deficiency by 2D speckle tracking echocardiography

Abstract: The systolic and diastolic functions of the LV in the patients with CAE and vitamin D deficiency were impaired as evaluated by 2DSTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…сопровождался увеличением ФВ ЛЖ на 2,73% [14]. Аналогичные данные были получены в работе Aghajani H, et al (2017), где было выявлено снижение показателей функции ЛЖ по данным допплер-ЭхоКГ у пациентов с дефицитом витамина Д [15]. Следует отметить, что прирост ФВ ЛЖ в данной работе был менее выражен, относительно результатов исследования EVITA, что, возможно, связано с более тяжелой коморбидностью больных ХОБЛ.…”
Section: Discussionunclassified
“…сопровождался увеличением ФВ ЛЖ на 2,73% [14]. Аналогичные данные были получены в работе Aghajani H, et al (2017), где было выявлено снижение показателей функции ЛЖ по данным допплер-ЭхоКГ у пациентов с дефицитом витамина Д [15]. Следует отметить, что прирост ФВ ЛЖ в данной работе был менее выражен, относительно результатов исследования EVITA, что, возможно, связано с более тяжелой коморбидностью больных ХОБЛ.…”
Section: Discussionunclassified
“…They also noted a negative correlation between VitD and the E/E' ratio, a LV filling pressure marker. 23 Recently, Aghajani et al, 24 evaluated the longitudinal left ventricular function in patients with coronary artery ectasia (CAE) and vitamin D deficiency by echocardiography. The results showed that LV systolic and diastolic function in patients with CAE and Vitamin D deficiency were impaired.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that LV systolic and diastolic function in patients with CAE and Vitamin D deficiency were impaired. 24 Another study on supplementation showed that D-deficient prediabetic African American males who were treated with highdose vitamin D2 were found to have attenuated increases in left atrial volume compared with controls over 12-month follow-up. 25 Our findings are in line with what is described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…More than 80% of CAE patients experience coronary artery disease (CAD) (1,3); their main symptoms include angina, myocardial infarction, arrhythmia, and sudden death, and most are treated under the principle of current guidelines for CAD (4,5). However, CAE is also characterized by obvious slow blood flow in dilated coronary arteries (6,7), increased inflammatory markers in peripheral blood (8), anomalies in other blood vessels (9)(10)(11), and decreased left ventricular diastolic function (12). Pathologically, CAE is characterized by the extensive destruction of the musculoelastic elements in the coronary wall (3,4).…”
Section: Introductionmentioning
confidence: 99%